Numerical Analysis on Paper Sheet Separation Using the Overlap Separation Mechanism - Hui CHENG; Hiroshi IKEDA; Kazushi YOSHIDA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
The overlap separation mechanism is widely used to separate paper sheets from each other in automatic teller machines. In this study, we first derived a formula used for expressing the normal separation condition of paper sheets. Then we analyzed the deformation force acting on the paper sheet surfaces by treating the paper sheet as an elastic beam and using Clapeyron's theorem of three moments. Furthermore, by using the finite element analysis software LS-DYNA, we developed a three-dimensional simulation method that can accurately reproduce normal separation, misfeeding, and double feeding behaviors. Finally, the effects of the main parameters on deformation force will be discussed. The results show that the deformation force is proportional to the overlap; the bigger the width of gate-roller or the distance of roller edges, the bigger the deformation force. Moreover, the width of the feed-roller has hardly any effect on deformation force. It is shown that separation defects obtained by the elastic beam model agree well with those obtained by the FE model.